Matrix resin, photoresist composition, photoresist as well as preparation method and application of photoresist
By using photoacid generators in the photoresist composition to promote the crosslinking reaction of the matrix resin, the problem of insufficient fineness of the photolithography process in the prior art is solved, and higher adhesion and fineness of the photolithography pattern are achieved.
Patent Information
- Application Number
- CN202411945189.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-27
AI Technical Summary
The prior art cannot provide a photoresist composition capable of achieving a more refined photolithography process.
A matrix resin and a photoresist composition are provided. By absorbing light energy under KrF excited laser radiation, the photoacid generator absorbs light energy and decomposes acids, thereby promoting the crosslinking reaction between epoxy groups and hydroxy groups in the matrix resin, and improving the crosslinking degree of the photoresist composition.
The crosslinking degree of photoresist composition is improved, the adhesion of the photolithographic patterns is enhanced, and a more refined photolithography process is achieved.
Smart Images

Figure BDA0005213474790000021 
Figure BDA0005213474790000031 
Figure BDA0005213474790000032
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of photoresists and relates to a matrix resin, a photoresist composition, a photoresist and a preparation method and application thereof. Background Art
[0002] The level of photolithography technology directly determines the quality of integrated circuit chips. The so-called photolithography technology is to use photoresist (photoresist) to expose under specific light source, and then transfer the pre-designed pattern on the mask to the substrate wafer through development, etching and other steps. The birth of an integrated circuit chip with excellent performance requires not only design innovation, but also advanced photolithography technology. Photoresist is a photosensitive material. Certain chemical reactions will occur during the exposure process (ultraviolet irradiation, etc.), causing the solubility of the exposed area in the developer to change, and then after development with the developer, a specific photolithography pattern composed of components and circuits is obtained. Photoresist is mainly composed of four parts: film-forming resin, photosensitive substance, solvent, and appropriate additives. Among them, film-forming resin is the main component of photoresist, which supports the entire photoresist, makes the photoresist resistant to etching, and has an important influence on the performance of photoresist.
[0003] The preparation method of photoresist is complex and there are many varieties. According to the difference in solubility of photoresist in developer before and after exposure, it can be divided into two categories: positive photoresist and negative photoresist. The chemical reaction of positive photoresist in the exposed area can lead to its enhanced solubility in the developer, and the mask-covered area left after development is the designed chip pattern; conversely, the chemical reaction of negative photoresist in the exposed area can reduce its solubility in the developer, while the mask-covered area can be soluble in the developer, thereby obtaining a chip pattern complementary to the mask.
[0004] Chinese patent application 200780029153.7 discloses a photoresist composition having ideal physical properties such as photosensitivity, resolution, residual film ratio and coating characteristics. Moreover, due to its excellent light transmittance, it can form a pattern with an ideal development profile and focus depth using a light source with a wavelength of 248nm (krypton fluoride KrF) or shorter in semiconductor processes or flat panel display processes, even if the photoresist composition is used in non-chemically amplified photoresists.
[0005] Chinese patent application 202111515560.7 discloses a method for forming a photoresist pattern and a photoresist structure. The method for forming a photoresist pattern includes forming a photoresist structure on a target layer, the photoresist structure including a photoresist layer disposed on the target layer, and a light wave transmission layer disposed on the photoresist layer; exposing the photoresist structure in a first medium to form an exposure image on the photoresist layer, and the light wave transmission layer is used to improve the photolithography resolution of the photoresist layer. The method for forming a photoresist pattern in this technology improves the resolution of the exposure image through the light wave transmission layer and improves the accuracy of the photoresist pattern.
[0006] However, the prior art cannot provide a photoresist composition that can realize a more sophisticated photolithography process. Summary of the invention
[0007] In view of the problems existing in the above-mentioned prior art, the object of the present invention is to provide a matrix resin, a photoresist composition, a photoresist and a preparation method and application thereof.
[0008] To achieve the above-mentioned object of the invention, on the one hand, the present invention provides a base resin, wherein the structural unit of the base resin is composed of the following groups:
[0009]
[0010] Preferably, the weight average molecular weight of the base resin is in the range of 2000-50000, more preferably 3000-30000, and even more preferably 20000-25000. More preferably, the weight average molecular weight is 23097-23497.
[0011] Preferably, the polymer dispersibility index (PDI) of the base resin is 1-5, more preferably 1-3. Further preferably, the PDI is 1.98-2.12.
[0012] The polymer dispersibility index (PDI) is defined as the ratio of the weight average molecular weight to the number average molecular weight of a polymer substance.
[0013] Preferably, the weight content of oxygen in the matrix resin is 1%-1.5%, more preferably 1.35%-1.37%.
[0014] Preferably, the epoxy value of the base resin is 0.2-0.8 mmol / g.
[0015] In another aspect, the present invention provides a method for preparing a base resin, comprising the following steps:
[0016] Styrene, p-phenoxystyrene, p-(ethylene oxide)styrene, a solvent and an initiator are mixed and heated for reaction to obtain a base resin.
[0017] Wherein, the chemical structural formula of the p-phenoxy styrene is as follows:
[0018]
[0019] The chemical structural formula of described p-(ethylene oxide) styrene is as follows:
[0020]
[0021] Preferably, the usage ratio of the solvent to the styrene is 1:0.8-1.2, more preferably 1:1, and the unit is L:mol.
[0022] Preferably, the initiator is an azo initiator, including but not limited to azobisisobutyronitrile, azobisisoheptylnitrile, azobisisobutylimidazoline hydrochloride, azobisisobutylamidine hydrochloride, azoisobutylcyanamide and dimethyl azobisisobutyrate.
[0023] More preferably, and as a specific example of the present invention, the initiator is azobisisoheptanonitrile.
[0024] Preferably, the molar ratio of styrene, p-phenoxystyrene and p-(ethylene oxide)styrene is 100:2.4-6.4:5.6-9.6. More preferably, and as a specific example of the present invention, the molar ratio of styrene, p-phenoxystyrene and p-(ethylene oxide)styrene is 100:4.4:7.6.
[0025] Preferably, the weight of the initiator is 0.5%-10% of the total weight of the styrene, p-phenoxystyrene and p-(ethylene oxide)styrene. More preferably, and as a specific example of the present invention, the weight of the initiator is 3% of the total weight of the styrene, p-phenoxystyrene and p-(ethylene oxide)styrene.
[0026] Preferably, the solvent is selected from at least one of toluene, xylene, diphenyl ether, dimethyl sulfoxide, ethyl acetate and ethyl lactate, more preferably ethyl acetate.
[0027] Preferably, the temperature of the heating reaction is 50-90°C, more preferably 60-80°C.
[0028] Preferably, the heating reaction time is 6-30 h, more preferably 8-20 h, and even more preferably 8-15 h.
[0029] On the other hand, the present invention provides a photoresist composition, comprising, by weight, 141-176 parts of a base resin, 29-64 parts of poly(4-vinylphenol), 6-10 parts of an acid generator, and 2000-2800 parts of an organic solvent;
[0030] Wherein, the base resin is the base resin prepared by the above-mentioned preparation method.
[0031] Preferably, the acid generator is a photoacid generator.
[0032] More preferably, the photoacid generator is selected from at least one of sulfonium salt acid generators, iodonium salt acid generators, diazomethane acid generators, and nitrobenzene sulfonate acid generators.
[0033] As an example of the present invention, the acid generator is diphenyliodonium hexafluorophosphate.
[0034] Preferably, and as an example of the present invention, the photoresist composition further comprises 5.1-24 parts by weight of a crosslinking agent; the crosslinking agent is selected from at least one of an etherified amino crosslinking agent and an etherified polyphenyl crosslinking agent.
[0035] More preferably, the etherified amino cross-linking agent is selected from etherified melamine cross-linking agents and etherified urea cross-linking agents.
[0036] More preferably, the etherified melamine cross-linking agent is Cymel 308.
[0037] More preferably, the etherified urea crosslinking agent is selected from at least one of 1,3-dimethoxymethyl-4,5-dimethoxyethylene urea, 1,3,4,6-tetrakis(methoxymethyl)glycoluril (TMMG), and 1,3-dimethoxy-1,3-dimethylurea.
[0038] More preferably, the etherified polyphenyl crosslinking agent is selected from at least one of 4,4'-(2,2-dipropyl)bis(2,6-bis(methoxymethyl)phenol) and 4,4',4"-(1,1,1-triethyl)tris(2,6-bis(methoxymethyl)phenol).
[0039] As an embodiment of the present invention, the cross-linking agent is 1,3,4,6-tetrakis(methoxymethyl)glycoluril. Its structural formula is:
[0040]
[0041] Preferably, the solvent is selected from at least one of alcohols, esters, ethers, aromatic hydrocarbons and ketones.
[0042] More preferably, the solvent is selected from at least one of propylene glycol monomethyl ether, diethylene glycol monoethyl ether, ethylene glycol monoethyl ether acetate, propylene glycol monomethyl ether acetate, n-hexanol, n-butanol, isopropanol, and diphenyl ether.
[0043] More preferably, the solvent is a mixture of propylene glycol monomethyl ether acetate and diphenyl ether.
[0044] Further preferably, and as an example of the present invention, the solvent is a mixture of propylene glycol monomethyl ether acetate and diphenyl ether in a volume ratio of 1:1.
[0045] Preferably, the photoresist composition further comprises 3-7 parts by weight of a photobase generator.
[0046] The photobase generator is selected from at least one of the following ingredients:
[0047]
[0048] More preferably, the photobase generator is selected from one of the following ingredients:
[0049]
[0050] More preferably, and as an example of the present invention, the photobase generator is
[0051]
[0052] Preferably, the photoresist composition further comprises 0.001-5 parts by weight of an additive.
[0053] The additive is selected from one or more of a stabilizer, a leveling agent, and a surfactant.
[0054] In another aspect, the present invention provides a photoresist made from the above-mentioned photoresist composition, preferably made by mixing the above-mentioned photoresist composition.
[0055] The present invention has no particular limitation on the order of mixing the components in the above-mentioned photoresist composition, as long as the purpose of the present invention can be achieved.
[0056] On the other hand, the present invention provides the use of the above-mentioned photoresist in forming a photoresist pattern, including a film forming process, an exposure process and a development process.
[0057] Preferably, the exposure is performed using a KrF laser.
[0058] Preferably, the application comprises the following steps:
[0059] S1, coating a photoresist on a substrate to obtain a coated back plate;
[0060] S2, baking the coated board obtained in step S1 at a temperature of 90-130° C. for 60-120 seconds to obtain a PEB board;
[0061] S3, exposure: the PEB board obtained in step S2 is exposed using a KrF exposure machine to obtain an exposed board;
[0062] S4, performing post-exposure baking on the exposed board obtained in step S3 at a temperature of 110-140° C. for a baking time of 60-120 seconds to obtain a PAB board;
[0063] S5, development: the PAB board obtained in step S4 is developed using a developer to obtain a circuit substrate product.
[0064] Preferably, in step S5, the developer is an aqueous solution of at least one of tetramethylammonium hydroxide, tetraethylammonium hydroxide and tetrabutylammonium hydroxide.
[0065] In the last aspect, the present invention provides the use of the above-mentioned base resin or the base resin prepared by the preparation method or the above-mentioned photoresist composition or the above-mentioned photoresist in the preparation of circuit substrates and integrated circuit boards.
[0066] Equivalent to the prior art, the present invention has the following beneficial effects:
[0067] 1. The present invention provides a photoresist composition, wherein the polymer component of the photoresist composition contains hydroxyl groups and epoxy groups. When the photoresist composition is irradiated by KrF excited state laser, the photoacid generator absorbs light energy and decomposes acid. During post-exposure baking, on the one hand, under the action of acid, ring-opening polymerization occurs between epoxy groups, causing polymer molecular chains to be cross-linked; on the other hand, the acid-catalyzed cross-linking agent reacts with the hydroxyl groups in the matrix resin to cross-link the polymer molecular chains. This improves the cross-linking degree of the photoresist composition, helps to improve the adhesion of the photolithography pattern, prevents it from being washed away, and thus realizes a more sophisticated photolithography process.
[0068] 2. The present invention adds a photobase generator to the photoresist composition to generate diethanolamine during the exposure process. The generated diethanolamine can help improve the H generated by the photoacid generator during the exposure process. + The problem of too fast migration is solved, thus avoiding the standing waves in the photolithography pattern and helping to improve the resolution of the photoresist. DETAILED DESCRIPTION
[0069] Terms and Claims of the Present Invention:
[0070] 1. The articles “a”, “an” and “the” include plural referents unless expressly limited to one or more referents otherwise.
[0071] 2. Numerical range: Unless otherwise expressly stated, all ranges or ratios disclosed herein will be understood to include any and all sub-ranges or sub-ratios contained therein. For example, a range or ratio of 1 to 30 stated should be considered to be included between a minimum value of 1 and a maximum value of 30, and any sub-range or sub-ratio, integer, decimal, or sub-range or sub-ratio consisting of integers or decimals including the end points.
[0072] The following non-limiting examples can enable those skilled in the art to more fully understand the present invention, but do not limit the present invention in any way. The following content is merely an exemplary description of the scope of the present invention, and those skilled in the art can make various changes and modifications to the present invention based on the disclosed content, which should also fall within the scope of the present invention.
[0073] The present invention is further described below by way of specific examples. The various chemical reagents used in the examples of the present invention are obtained through conventional commercial channels unless otherwise specified. Unless otherwise specified, the contents described below are all weight contents. Unless otherwise specified, it is understood that the process is carried out at room temperature.
[0074] In the following examples, all starting materials are commercially available or synthesized using known procedures.
[0075] The codes and chemical structural formulas of the compounds in the following examples and comparative examples correspond to those shown in Table 1:
[0076] Table 1
[0077]
[0078]
[0079] In the following examples and comparative examples, the poly(4-vinylphenol) used is a commercially available product (brand: Adamas) with a weight average molecular weight Mw of about 11,000.
[0080] Example 1
[0081] A photoresist having the following composition.
[0082] 15.85 g of base resin 1, 4.65 g of poly(4-vinylphenol), 0.8 g of diphenyliodonium hexafluorophosphate, 1.5 g of compound 1, 0.5 g of compound 5 and 240 g of propylene glycol monomethyl ether acetate and diphenyl ether in a volume ratio of 1:1 were mixed to obtain a photoresist. All of the above ingredients were mixed to obtain a photoresist.
[0083] Wherein, the preparation method of base resin 1 is as follows:
[0084] 100 mmol styrene (about 10.42 g), 4.4 mmol p-phenoxystyrene (about 0.863 g), 7.6 mmol p-(epoxyethyl)styrene (about 1.11 g), 0.37 g azobisisoheptanenitrile (equivalent to 3% of the monomer mass) and 100 mL ethyl acetate were mixed evenly, heated to 60° C., and refluxed for 10 hours. Methanol was added for precipitation, filtered, washed three times with water and methanol respectively, and dried to obtain base resin 1 (yield 10.9 g).
[0085] It is worth noting that in the various embodiments and comparative examples of the present invention, the method for preparing the matrix resin can expand the reaction scale by proportionally increasing the amount of each component within a reasonable range and / or repeating the reaction process to obtain a sufficient amount of the product matrix resin.
[0086] Example 2
[0087] Compared with Example 1, the difference is that the dosage of each component in the photoresist is changed to the following:
[0088] A mixture obtained by mixing 14.1 g of base resin 1, 6.4 g of poly(4-vinylphenol), 0.6 g of diphenyliodonium hexafluorophosphate, 2.4 g of compound 1, 0.3 g of compound 5 and 280 g of propylene glycol monomethyl ether acetate and diphenyl ether in a volume ratio of 1:1.
[0089] The rest are the same.
[0090] Example 3
[0091] Compared with Example 1, the difference is that the dosage of each component in the photoresist is changed to the following:
[0092] A mixture obtained by mixing 17.6 g of base resin 1, 2.9 g of poly(4-vinylphenol), 1 g of diphenyliodonium hexafluorophosphate, 0.51 g of compound 1, 0.7 g of compound 5 and 200 g of propylene glycol monomethyl ether acetate and diphenyl ether in a volume ratio of 1:1.
[0093] The rest are the same.
[0094] Example 4
[0095] Compared with Example 1, the difference is that 0.5 g of compound 5 is replaced by a mixture of 0.25 g of compound 3 and 0.25 g of compound 4, and the rest are the same.
[0096] Example 5
[0097] Compared with Example 1, the difference is that 0.5 g of compound 5 is replaced by 0.5 g of compound 2, and the rest is the same.
[0098] Example 6
[0099] Compared with Example 1, the difference is that the base resin 1 is replaced by the base resin 2 of the same weight.
[0100] The preparation method of base resin 2 is as follows:
[0101] 100 mmol styrene (about 10.42 g), 6.4 mmol p-phenoxystyrene (about 1.256 g), 5.6 mmol p-(ethylene oxide)styrene (about 0.819 g), 0.625 g azobisisoheptanenitrile (equivalent to 5% of the monomer mass) and 100 mL ethyl acetate were mixed evenly, heated to 60°C, and kept under reflux for 10 hours. Methanol was added for precipitation, filtered, washed three times with water and methanol respectively, and dried to obtain base resin 2 (yield 10.5 g).
[0102] Example 7
[0103] Compared with Example 1, the difference is that the base resin 1 is replaced by the base resin 3 of the same weight.
[0104] The preparation method of base resin 3 is as follows:
[0105] 100 mmol styrene (about 10.42 g), 2.4 mmol p-phenoxystyrene (about 0.471 g), 9.6 mmol p-(epoxyethyl)styrene (about 1.4 g), 0.245 g azobisisoheptanenitrile (equivalent to 2% of the monomer mass) and 100 mL ethyl acetate were mixed evenly, heated to 60°C, and kept under reflux for 10 hours. Methanol was added for precipitation, filtered, washed three times with water and methanol respectively, and dried to obtain base resin 3 (yield 10.0 g).
[0106] Comparative Example 1
[0107] Compared with Example 1, the difference is that Compound 1 is omitted, and the rest is the same.
[0108] Comparative Example 2
[0109] Compared with Example 1, the difference is that the base resin 1 is replaced by the base resin 4 of the same weight.
[0110] The synthesis method of base resin 4 is as follows
[0111] 100 mmol styrene (about 10.42 g), 8.8 mmol p-phenoxystyrene (about 1.72 g), 3.2 mmol p-(epoxyethyl)styrene (about 0.468 g), 0.378 g azobisisoheptanenitrile (equivalent to 3% of the monomer mass) and 100 mL ethyl acetate were mixed evenly, heated to 60° C., and refluxed for 10 hours. Methanol was added for precipitation, filtered, washed three times with water and methanol respectively, and dried to obtain base resin 1 (yield 10.0 g).
[0112] Comparative Example 3
[0113] Compared with Example 1, the difference is that the base resin 1 is replaced by the base resin 5 of the same weight.
[0114] The synthesis method of the matrix resin 5 is as follows
[0115] 100 mmol styrene (about 10.42 g), 7.7 mmol p-phenoxystyrene (about 1.51 g), 13.3 mmol p-(ethylene oxide)styrene (about 1.94 g), 0.416 g azobisisoheptanenitrile (equivalent to 3% of the monomer mass) and 100 mL ethyl acetate were mixed evenly, heated to 60°C, and kept under reflux for 10 hours. Methanol was added for precipitation, filtered, washed three times with water and methanol respectively, and dried to obtain base resin 1 (yield 10.6 g). Comparative Example 4
[0116] Compared with Example 1, the difference is that poly(4-vinylphenol) is omitted, the weight of the base resin 1 is changed to 20.5 g, and the rest is the same.
[0117] Comparative Example 5
[0118] Compared with Example 1, the difference is that the base resin 1 is omitted, the amount of poly (4-vinylphenol) is changed to 20.5g, and the rest is the same.
[0119] Comparative Example 6
[0120] Compared with Example 1, the difference is that the base resin 1 is replaced by polystyrene of equal weight, and the composition of other photoresists is the same.
[0121] The synthesis method of polystyrene is as follows:
[0122] 100 mmol styrene (about 10.42 g), 0.31 g azobisisoheptanitrile (equivalent to 3% of the monomer mass) and 100 mL ethyl acetate were mixed evenly, heated to 60°C, and kept under reflux for 10 hours. Methanol was added for precipitation, filtered, washed three times with water and methanol respectively, and dried to obtain polystyrene (yield 9.1 g).
[0123] Application Examples
[0124] The photoresist composition was evenly spin-coated on the surface of the copper-plated silicon wafer, and the film thickness was controlled at 0.3μm and 1.0μm respectively; it was heated on a hot plate at 100°C for 60s, exposed with a KrF exposure machine, and then developed with a 1.1% tetrabutylammonium hydroxide aqueous solution, and heated on a hot plate at 110°C for 90s to harden the film.
[0125] Effect evaluation
[0126] 1. Structural characterization of matrix resin
[0127] The structures of base resin 1 prepared in Example 1, base resin 2 prepared in Example 6, base resin 3 prepared in Example 7, base resin 4 prepared in Comparative Example 2, and base resin 5 prepared in Comparative Example 3 were characterized respectively.
[0128] 1.1. Number average molecular weight, weight average molecular weight and polymer dispersity index (PDI) of matrix resin
[0129] With reference to the prior art "Study on the Determination of Molecular Weight and Molecular Weight Distribution of Polystyrene Using Rheometer" (Analysis and Testing Technology and Instruments, September 2007, Vol. 13, No. 3), the number average molecular weight Mn, weight average molecular weight Mw and polymer dispersity index PDI of matrix resin 1-matrix resin 5 were characterized.
[0130] PDI=Mw÷Mn.
[0131] The test results are shown in Table 2:
[0132] Table 2
[0133] Group Base resin 1 Base resin 2 Base resin 3 Base resin 4 Base resin 5 M 23497 23214 23097 23583 25427 Mn 11864 10929 11056 10219 11913 PDI 1.98 2.12 2.09 2.31 2.13
[0134] 1.2. Epoxy value of base resin
[0135] The epoxy value of the matrix resin is tested by the improved hydrochloric acid acetone method. The specific method is as follows:
[0136] Take concentrated hydrochloric acid and acetone in a volume ratio of 1:40 and mix them to obtain a hydrochloric acid acetone solution. Take 0.5g of each base resin, add 20mL of hydrochloric acid acetone solution respectively, and place on a shaker to fully react for 0.5h. Hydrogen chloride reacts with epoxy groups to undergo a ring-opening addition reaction, and one epoxy group exists for each chlorine atom added to the polymer. Volatilize the hydrochloric acid and acetone in a fume hood, add a small amount of chromatographic grade anhydrous ethanol twice respectively, wash, and evaporate to obtain the base resin after chlorine addition. The chlorine content (unit: mmol / g) in the base resin after chlorine addition can be obtained by X-ray fluorescence spectrometry (XRF) detection, and the epoxy value of the base resin can be converted by the following formula.
[0137] Epoxy value = ACl ÷(1-A Cl ×M HCl ).
[0138] Among them, A Cl is the chlorine content in the matrix resin after chlorine addition (mmol / g), M HCl is the molecular weight of hydrogen chloride, in g / mol. (For convenience of calculation, it can be converted into g / mmol, 1g / mol = 10 -3 g / mmol. )
[0139] 1.3. Oxygen content of matrix resin
[0140] The oxygen content of each matrix resin can be determined by the combustion method. The oxygen content is the total content of phenoxy and epoxy groups in the polymer. Combined with the epoxy value of the matrix resin, the value range of each structural unit in the polymer can be roughly determined.
[0141] The epoxy value and oxygen weight content (oxygen content) of the matrix resin are shown in Table 3:
[0142] Table 3
[0143] Group Base resin 1 Base resin 2 Base resin 3 Base resin 4 Base resin 5 Epoxide value (mmol / g) 0.608 0.347 0.702 0.173 0.895 Oxygen content (%) 1.361 1.355 1.364 1.336 2.180
[0144] 2. Adhesion test
[0145] 2.1. Hundred-grid test
[0146] Use a grid knife to draw 10×10 100 small squares of 1mm×1mm on the surface of the test sample. Each line is deep enough to reach the bottom layer where the photoresist and the copper-plated silicon wafer are combined. Use 3M 600 adhesive tape to firmly stick the small grid to be tested, then quickly tear off the tape and conduct two tests at the same location. Count the peeling situation and conduct adhesion rating. The rating standards are as follows:
[0147] Grade 5B: The edges of the cut are completely smooth, without any peeling on the lattice edges.
[0148] Grade 4B: There is small flakes at the intersection of the cuts, and the actual damage in the cross-cut area is ≤5%.
[0149] Grade 3B: The edges and / or intersections of the cuts are peeled off, with an area greater than 5%-15%.
[0150] Grade 2B: There is partial peeling or large-scale peeling along the edge of the cut, and the peeling area exceeds 15%-35%.
[0151] Grade 1B: Large pieces of the cut edge are peeling off, or some squares are partially or completely peeling off, with an area greater than 35%-65%.
[0152] Grade 0B: There are pieces of film falling off at the edges and intersections of the scribe lines, and the total falling off area is greater than 65%.
[0153] The test results of adhesion of each group are shown in Table 4:
[0154] Table 4
[0155]
[0156]
[0157] 2.2. Undercut phenomenon test.
[0158] Undercutting refers to the phenomenon that the edge of the photoresist film layer and the junction with the substrate are sunken inward. The reasons for the undercutting phenomenon include the contraction of the photoresist film layer itself and / or the inward depression of the edge due to the influence of the etchant residue. The adhesion of the photoresist film with undercutting to the substrate is lower. The adhesion of the photoresist can be evaluated by evaluating the occurrence rate of undercutting.
[0159] The substrates provided in Examples 1 to 7 and Comparative Examples 1 to 6 were longitudinally sectioned, with 5 samples in each group taken as parallel experiments, and then the shapes of the longitudinal sections were observed using a scanning electron microscope to check for undercutting. The results are shown in Table 5.
[0160] Table 5
[0161]
[0162]
[0163] It can be seen that compared with the comparative examples, the photoresists provided in Examples 1 to 7 have stronger adhesion to the substrate.
[0164] 3. Resolution evaluation after photolithography
[0165] Graphic inspection was performed using a critical dimension scanning electron microscope (CD-SEM). The optimal exposure energy is defined as the exposure energy (mJ / cm2) when the exposure line width is the target resolution at a specified resolution. 2 ). The maximum resolution of photoresist is defined as the minimum feature size formed on a silicon wafer at the optimal exposure energy. The line edge roughness (LER) of the 160nm L / S pattern was evaluated by CD-SEM.
[0166] The experimental results of 0.3 μm thick film are shown in Table 6:
[0167] Table 6
[0168] Group Maximum resolution (nm) Line edge roughness (nm) Example 1 161.2 6.6 Example 2 159.6 6.7 Example 3 160.9 6.9 Example 4 159.3 6.2 Example 5 159.7 5.9 Example 6 160.1 6.0 Example 7 160.3 6.4 Comparative Example 1 334.1 7.0 Comparative Example 2 379.0 6.9 Comparative Example 3 383.8 6.9 Comparative Example 4 494.4 7.8 Comparative Example 5 480.8 7.9 Comparative Example 6 449.7 9.7
[0169] The experimental results of 1 μm thick film are shown in Table 7:
[0170] Table 7
[0171]
[0172]
[0173] It can be seen that, compared with the comparative examples, the embodiments can achieve a more refined photolithography effect after the photoresist is exposed to light.
[0174] Finally, it should be noted that the above content is only used to illustrate the technical solution of the present invention, rather than to limit the scope of protection of the present invention. Simple modifications or equivalent substitutions of the technical solution of the present invention by ordinary technicians in this field do not deviate from the essence and scope of the technical solution of the present invention.
Claims
1. A matrix resin, characterized in that: The structural units of the base resin are composed of the following groups: The weight average molecular weight of the base resin is in the range of 2000-50000; the weight content of oxygen element in the base resin is 1%-1.5%; and the epoxy value of the base resin is 0.2-0.8 mmol / g.
2. The method for preparing the matrix resin according to claim 1, characterized in that: The following steps are involved: Styrene, p-phenoxystyrene, p-(ethylene oxide)styrene, a solvent and an initiator are mixed and heated for reaction to obtain a base resin.
3. The preparation method according to claim 2, characterized in that: The molar ratio of styrene, p-phenoxystyrene and p-(ethylene oxide)styrene is 100:2.4-6.4:5.6-9.6, the weight of the initiator is 0.5%-10% of the sum of the weights of styrene, p-phenoxystyrene and p-(ethylene oxide)styrene; the solvent is selected from at least one of toluene, xylene, diphenyl ether, dimethyl sulfoxide, ethyl acetate and ethyl lactate; the temperature of the heating reaction is 50-90°C, and the time of the heating reaction is 6-30h.
4. A photoresist composition, characterized in that The composition comprises, by weight, 141-176 parts of a base resin, 29-64 parts of poly(4-vinylphenol), 6-10 parts of an acid generator and 2000-2800 parts of an organic solvent; Wherein, the base resin is the base resin described in claim 1 or the base resin prepared by the preparation method described in any one of claims 2-3.
5. The photoresist composition according to claim 4, characterized in that The photobase generator further comprises 3-7 parts by weight, wherein the photobase generator is selected from at least one of the following components: The solvent is selected from at least one of alcohols, esters, ethers, aromatic hydrocarbons and ketones.
6. The photoresist composition according to claim 4 or 5, characterized in that: The invention also comprises 5.1-24 parts by weight of a cross-linking agent, wherein the cross-linking agent is selected from at least one of an etherified amino cross-linking agent and an etherified polyphenyl cross-linking agent.
7. A photoresist, characterized in that: Made from the photoresist composition described in any one of claims 4 to 6.
8. Use of the photoresist according to claim 7 in forming a photoresist pattern, characterized in that: It includes film making process, exposure process and development process.
9. The use according to claim 8, characterized in that: The following steps are involved: S1, coating the photoresist composition on a substrate to obtain a coated back plate; S2, baking the coated board obtained in step S1 at a temperature of 90-130° C. for 60-120 seconds to obtain a PEB board; S3, exposure: the PEB board obtained in step S2 is exposed using a KrF exposure machine to obtain an exposed board; S4, performing post-exposure baking on the exposed board obtained in step S3 at a temperature of 110-140° C. for a baking time of 60-120 seconds to obtain a PAB board; S5, development: the PAB board obtained in step S4 is developed using a developer to obtain a circuit substrate product.
10. Use of the base resin described in claim 1, or the base resin prepared by the preparation method described in any one of claims 2-3, or the photoresist composition described in any one of claims 4-6, or the photoresist described in claim 7 in the preparation of circuit substrates and integrated circuit boards.
Citation Information
Patent Citations
Photoresist composition and patterning method thereof
CN101501570A
Method for forming photoresist pattern and photoresist structure
CN116263564A
Polyolefin epoxy resin, preparation method and application
CN108129593A
Negative photoresist composition as well as preparation method and application thereof
CN117631453A
Curable composition for nanoimprint, and cured body and manufacturing method thereof
JP2009206197A